Spleen tissue changes after restraint stress: effects of aerobic exercise training. (3rd September 2021) - Feriani, Daniele J.; Sousa, Andressa S.; Delbin, Maria Andreia; Ruberti, Olívia M.; Crestani, Carlos C.; Rodrigues, Bruno
Abstract: Inflammation has been described as a prominent mechanism involved in dysfunctions and diseases evoked by chronic stress. Notably, the spleen is an immune organ controlled by sympathetic and glucocorticoid mechanisms, but the impact of chronic stress in the spleen is not entirely understood. Besides, the impact of aerobic exercise training on the effects of chronic stress in the spleen has never been reported. Therefore, this study aimed to assess the changes caused in the spleen by repeated restraint stress and the effect of aerobic exercise training performed after a period of chronic restraint stress in rats. We identified that daily exposure to restraint stress (120 min per session, for 14 consecutive days) increased corticosterone and noradrenaline content, gene expression of glucocorticoid and β2 -adrenergic receptors, TNF-α and IL-6 levels, and increased pro-oxidant substances in the spleen. Circulating levels of corticosterone were also increased in chronically stressed animals. Exercise training (1 h a day/5 days per week, for 60 days) increased glucocorticoid receptor gene expression, interleukin (IL)-10 and antioxidant mechanisms in the spleen. Exercise also decreased splenic noradrenaline, tumoral necrosis factor (TNF)-α, and IL-6 contents. Lastly, the effects of repeated restraint stress in the spleen were mitigated in animals subjected to aerobic training. Taken together, the results reported in the present study indicate that aerobic exercise training is a relevant non-pharmacological therapeutic approach to dysfunctions in the spleen caused by a period of stress. LAY SUMMARY: Daily exposure to restraint stress increased corticosterone and noradrenaline content, gene expression of glucocorticoid and β2-adrenergic receptors, inflammatory cytokines, and increased pro-oxidant substances in the spleen. Exercise training increased glucocorticoid receptor gene expression, interleukin (IL)-10, and antioxidant mechanisms in the spleen. Exercise also decreased splenic noradrenalin and inflammatory cytokines. The effects of repeated restraint stress in the spleen were mitigated in animals subjected to aerobic training.